Effects of Salinity and Temperature on the Growth, Toxin Production, and Akinete Germination of the Cyanobacterium Nodularia spumigena - Silveira, Savênia B.; Odebrecht, Clarisse (Frontiers in Marine Science, 2019)
Harmful blooms of the cyanobacterium Nodularia spumigena occur in several parts of the world, and this species is notorious for its ability to produce cyanotoxins, such as nodularin. This species is also able to perform akinete differentiation, thus favoring the success of their populations under adverse conditions. In southern Brazil, N. spumigena has developed large blooms in experimental shrimp production farms. In this study, we implemented an experiment to evaluate the influence of salinity and temperature on several physiological attributes of a Brazilian strain of N. spumigena: cell growth, nodularin production, the ability to form akinetes and germination potential. A factorial experiment (3x4) was conducted to test the effects of temperature (15, 23, and 30 °C) and salinity (1, 7, 15, and 30 ppm) on the growth, production of nodularin and the differentiation of akinetes. The germination potential of the akinetes was tested after incubation for 30, 60, 90, 120, 180 and 360 days at 4 °C in the dark. N. spumigena grew under a wide range of salinity and temperatures, but salinity had a greater influence. The highest cell densities at the temperatures tested were observed at salinity 7 ppm and the lowest at salinity 1 ppm. The toxin nodularin was produced in all treatments, but there was an inverse relationship between the content of nodularin per cell and cell density. The akinetes were also differentiated in all the treatments, with the exception of S1T30. However, the largest proportion of akinetes (65% of the cells) was observed in the treatment with low cell growth at salinity 15 and 15 °C, possibly indicating an effort of the population to survive over the long term. The akinetes germinated in all treatments, but those cultivated at salinity 7 and 15 ppm (except S15T30) showed a higher percentage of germination and, in contrast, the lowest germination rate was observed in the treatments with salinity 1 ppm. Thus, the low salinity (1) at all the temperatures tested has the potential to inhibit N. spumigena blooms, since it hampers cell growth and the formation of akinetes.